2019
DOI: 10.1016/s1473-3099(18)30790-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of mass drug administration with ivermectin for control of scabies and impetigo, with coadministration of azithromycin: a single-arm community intervention trial

Abstract: Summary Background In small community-based trials, mass drug administration of ivermectin has been shown to substantially decrease the prevalence of both scabies and secondary impetigo; however, their effect at large scale is untested. Additionally, combined mass administration of drugs for two or more neglected diseases has potential practical advantages, but efficacy of potential combinations should be confirmed. Methods The azithromycin ivermectin mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
106
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 28 publications
5
106
0
Order By: Relevance
“…Further work in the Solomon Islands using ivermectin-based MDA in a much larger population reported reductions in scabies prevalence of around 90%, and in impetigo prevalence of around 75%. 14,130 Conversely, ivermectin-based MDA for scabies in northern Australia was not associated with a sustained reduction in prevalence. 79 Implementation research of integration of scabies control with other NTDs, particularly those affecting the skin, has the potential to demonstrate cost-efficient delivery of multiple health interventions.…”
Section: Population-level Controlmentioning
confidence: 97%
“…Further work in the Solomon Islands using ivermectin-based MDA in a much larger population reported reductions in scabies prevalence of around 90%, and in impetigo prevalence of around 75%. 14,130 Conversely, ivermectin-based MDA for scabies in northern Australia was not associated with a sustained reduction in prevalence. 79 Implementation research of integration of scabies control with other NTDs, particularly those affecting the skin, has the potential to demonstrate cost-efficient delivery of multiple health interventions.…”
Section: Population-level Controlmentioning
confidence: 97%
“…And a comparison of outpatient attendance at government clinics across the province in the 3 months before and after mass drug administration showed that the number of people presenting with skin sores, boils, and abscesses decreased by 50·9% (95% CI 48·6-53·1). 9 Compared with interventions in individuals, a lot of data is now available in endemic or epidemic settings from mass drug administration for treatment of scabies, whether adults or children, or other diseaseseg, onchocerciasis. 11,12 Which drug should be used for scabies and whether it should be combined with antibiotics are important decisions.…”
Section: Control Of Scabies and Secondary Impetigo: Optimising Treatmmentioning
confidence: 99%
“…Scabies is historically a challenging global infectious disease, for which acaricides are currently used as measures of controlling the scabies mite [12,13]; however, the unreasonable use of acaricides can lead to the development of drug resistance, toxicity, and associated side-effects [14,15]. Therefore, the development of a vaccine remains a high priority for global research.…”
Section: Introductionmentioning
confidence: 99%